STRATEGI PEMASARAN ONE DAY EVENT UMKM KULINER: ANALISIS BAURAN PEMASARAN (4P) PADA DIMSUM MICI DI CAR FREE DAY ( CFD ) - Zainarti Zainarti; Adina Litriwani; Aditya Putra Piliang; Alfian Khoiri Malau (CV. KAMPUS AKADEMIK PUBLISING, 2025)
One Day events such as Car Free Day (CFD) present a strategic opportunity for culinary MSMEs to directly introduce or promote their products in a short time. This study aims to analyze the marketing strategy of Dimsum Mici during Car Free Day (CFD) activities using the marketing mix (4P) approach: product, price, place, and promotion. This research was conducted using a descriptive qualitative approach combining field studies and library research. The results indicate that the product offered, Dimsum Mici, offers a variety of practical menu items that meet market tastes and quality that can compete with similar businesses. The strategy for affordable pricing is flexible and tailored to the purchasing power of the public attending Car Free Day (CFD). In terms of location, the stand's strategic and easily visible location can increase visitor opportunities. Meanwhile, the promotional strategy utilizes social media, direct sales, and attractive presentations to attract customers. Overall, the implementation of the marketing mix (4P) has proven effective in increasing consumer appeal, product visibility, and sales volume during one-day events such as Car Free Day. The research findings show that properly implemented 4P strategy integration can have a direct impact on increasing purchasing interest in a short-term marketing context. This research also provides insight into how culinary MSMEscan optimally utilize temporary or daily events as a means to expand their market, introduce products directly, and increase sales quickly.